Investigating Knowledge, Attitudes, and Perceptions of SARS-CoV-2 Vaccine Hesitancy among Pregnant Women in Soweto, South Africa - Maccarthy, Samuel Oluwasegun (University of the Witwatersrand, Johannesburg, 2024)
Pregnant women face heightened risks of severe COVID-19 consequences, making vaccination vital for their protection. In South Africa, despite government initiatives, vaccine hesitancy persists among pregnant women, hindering widespread coverage. This study delves into the knowledge, attitudes, and perceptions of COVID-19 vaccines among 60 unvaccinated pregnant women in Soweto, South Africa. It aims to identify influencers shaping their vaccine decisions, addressing a critical gap in understanding hesitancy in this vulnerable group. Data from a validated questionnaire reveal diverse information sources, with media being primary. Safety concerns emerge as the foremost hesitancy factor, and "personal decision" is a key influencer. Applying the 3C Model, the study unveils crucial factors guiding pregnant women's COVID-19 vaccination choices, providing insights for targeted public health strategies to address hesitancy in this susceptible population.
A research report submitted in fulfillment of the requirements for the Master of Medicine, in the Faculty of Health Sciences, School of Phathology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; SARS-CoV-2 Vaccine Hesitancy; Pregnant Women; South Africa; SDG-3: Good health and well-being